Pengaruh Bimbingan Orang Tua Dan Fasilitas BelajarTerhadap Prestasi Belajar IPA Siswa Kelas AtasSD Muhammadiyah 2 Kauman SurakartaTahun 2015/2016 - MAULITA, RINA (2016)
This study aims to determine (1) the effect of parental guidance on learning achievement. (2) the effect of learning facilities on the learning achievement. (3) the effect of parental guidance and learning facilities on the learning achievement. This type of research is a quantitative research using a survey method. Subjects in this study students upper SD Kauman Muhammadiyah 2 Surakarta. Mechanical testing instruments used are validity and reliability testing. Techniques used prerequisite test is the test of normality and linearity. Data analysis technique used is multiple regression analysis, t- test, F test, the coefficient of determination, and look for the amount of donations given. Based on the analysis of data obtained by multiple linear regression equation as follows: Y = 53.952 + 0,184X1 + 0,091X2, it means learning achievement dipengaruji by parental guidance and learning facilities. Based on the analysis and discussion can be concluded that: (1) the parental influence on science learning achievement. This is proven by the results of the calculation thitung> t table (2,713> 2,012) and ρ-value <0.05 (0.009 <0.05). (2) learning facilities affect the learning achievement IPA. This is proven by the results of the calculation thitung> t table (2,537> 2,012) and ρ-value <0.05 (0.015 <0.05). (3) parental guidance and learning facility jointly positive effect on learning achievement IPA. This is proven by the results of the calculation of F count> F table (26.346> 3.19) and the value of ρ-value <0.05 (0.000 <0.05). (4) The calculation for R2 values of 0.529, meaning that learning achievement IPA influenced by parental guidance and learning facilities by 52.9% while the remaining 47.1% is influenced by other than parental guidance and learning facilities that are not investigated in this study.